The Effect of Internal Control on Tax Avoidance With Family Ownership and Environmental Uncertainty as Moderating Variables - Bagas Hidayat; Anis Chariri (Tax Accounting Applied Journal, 2025)
Tax avoidance is one of the methods used by taxpayers to legally prevent tax payments by reducing the tax burden so as not to violate tax regulations. This is a significant problem for the country, as a lack of state revenue can cause national development plans to be delayed. Therefore, this study aims to determine the effect of internal control on tax avoidance and to investigate whether family ownership and environmental uncertainty moderate the relationship between internal control and tax avoidance.This study uses a quantitative method. The research population consists of oil and gas sector companies listed on the Indonesia Stock Exchange from 2021 to 2024. The sampling technique employed is purposive sampling, and the sample comprises 22 companies. The data analysis method employed is simple linear regression analysis, assisted by SPSS version 26.Based on the statistical tests conducted in this study, the results indicate that internal control has a significant negative effect on tax avoidance. Family ownership does not moderate the relationship between internal control and tax avoidance. Environmental uncertainty does not moderate the effect of internal control on tax avoidance.